The effect of education on the level of knowledge regarding the disposal of expired medications among the community of Cipinang Muara - Dhega Rhefaldy Dermawan; Anna Uswatun Hasanah Rochjana; Amalina Fakhriah (Indonesian Journal of Health Science, 2026)
Improper disposal of expired medication remains a community issue that poses potential risks to health and the environment, particularly when conducted without appropriate pharmaceutical waste management procedures. This study aimed to determine the impact of education on the community's level of knowledge regarding the disposal of expired medication in Cipinang Muara (RT 06 and RT 07, RW 04), East Jakarta. A pre-experimental, one-group pre-test/post-test design with a cross-sectional approach was employed. A sample of 72 respondents was selected using purposive sampling. Data were collected via a questionnaire that had undergone validity and reliability testing. A Shapiro-Wilk normality test revealed that the pre-test data were normally distributed, whereas the post-test data were not; consequently, the Wilcoxon Signed-Rank Test was used for analysis. The results indicated that prior to the educational intervention, knowledge levels fell predominantly into the "poor" (48.61%) and "fair" (19.44%) categories, with 31.95% falling into the "good" category. Following the intervention, all respondents (100%) were classified in the "good" category. The Wilcoxon Signed-Rank Test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference in knowledge levels before and after the education. Thus, the educational intervention was effective in increasing community knowledge regarding the disposal of expired medication. These findings underscore the importance of continuous educational programs as a preventive measure to support safe household pharmaceutical waste management for the benefit of health and the environment.